Effects of Oxytocin on Facial Expression and Identity Working Memory Are Found in Females but Not Males - Yue, Tong; Yue, Caizhen; Liu, Guangyuan; Huang, Xiting (Frontiers in Neuroscience, 2018)
Although oxytocin (OXT) has been shown to increase the ability of face perception and processing, no study has explored whether it could improve the performance of working memory for emotional expression information in men and women. In this double-blind, placebo-controlled, mixed-design study, we investigated the effects of OXT on temporary maintenance/manipulation of facial information through a facial expression (EMO) vs. identity (ID) working memory task, both for males (N=45) and females(N=46). Our results showed that in female participants, OXT increased the accuracy of the recognition of faces displaying angry and happy emotions, in the EMO tasks, and also reduced the response time to negative emotional faces, in the ID task. However, the above effects were not present in male subjects. These results indicate that OXT may increase the efficiency of working memory in face processing and this trend is reflected in females rather than in males. This study provides novel evidence for the sexually dimorphic effects of OXT on social cognition.